The role of effective factors on suicidal tendency of women in Turkey - Kılıçarslan, Şerife; Çelik, Sefa; Güngör, Abdullah Y.; Alkan, Ömer (Frontiers in Public Health, 2024)
Background/Aim This study aims to identify the variables that influence the suicidal tendency of women who are married, have had a relationship or are currently in a relationship in Turkey. Methods This study uses cross-sectional data from the 2014 Hacettepe University Institute of Population Studies National Research on Domestic Violence Against Women in Turkey. Data from 6,458 women between the ages of 15 and 49 were analyzed in this dataset. Binary logistic regression was used to determine the factors influencing women’s suicidal tendencies. Results Based on the analysis’s findings, age, education level, health status, number of children, the sector in which the spouse/partner works, the drinking status of the spouse/partner, the situation where the spouse/partner fights with another man in a way that involves physical violence, the cheating status of the spouse/partner, the controlling behaviour of the spouse/partner, exposure to various types of violence by both the spouse/partner and someone other than the partner, and the household income level variables were found to be associated with the suicidal tendency of women. Conclusion Prioritizing women who are, in particular, between the ages of 15 and 24, live in the south of Turkey, have a high school education, are in poor health, are childless, have low household incomes, live with an unemployed spouse or partner, and are exposed to various forms of violence from their partner or other sources can be achieved more effective results in reducing and preventing women’s suicidal behaviors.